Task-Based Language Learning: Old Approach, New Style. A New Lesson to Learn - Mónica Rodríguez-Bonces; Jeisson Rodríguez-Bonces (Universidad Nacional de Colombia, 2010)
This paper provides an overview of Task-Based Language Learning (TBL) and its use in the teaching and learning of foreign languages. It begins by defining the concept of TBL, followed by a presentation of its framework and implications, and finally, a lesson plan based on TBL. The article presents an additional stage to be considered when planning a task-based lesson: the one of formal and informal assessment. The rubrics and a self-evaluation format appear as an additional constituent of any task cycle.